2010
DOI: 10.1007/s10661-010-1740-9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fractions, sorption characteristics, and its release in the sediments of Baiyangdian Lake, China

Abstract: Sediment phosphorus (P) fractions and sorption characteristics and P release from intact sediment cores of Baiyangdian Lake in North China in spring 2009 were investigated. Results of chemical fractionation showed that total P (TP) content in sediment ranged from 443 to 611 mg kg( -1). Of the P fractions including inorganic P (IP) and organic P (OP), IP was a dominant component of TP and present in the form of P bounded to calcium (Ca-P) while the bioavailable P content bounded to Al, Fe, and Mn oxides and hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…For instance, the concentration of total phosphorus in sediments is between 152.18 mg/kg and 275.12 mg/kg in the Antalya Lake of Turkey, and the contamination risk is low [38]. The concentration of sediment phosphorus ranges from 443 mg/kg to 611 mg/kg in Baiyangdian Lake, which has become a potential factor of water eutrophication [16]. Similarly, sediment P concentration is between 390 mg/kg and 810 mg/kg in the Three Gorges reservoir [15].…”
Section: Environment Influence Of Sediment Pmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the concentration of total phosphorus in sediments is between 152.18 mg/kg and 275.12 mg/kg in the Antalya Lake of Turkey, and the contamination risk is low [38]. The concentration of sediment phosphorus ranges from 443 mg/kg to 611 mg/kg in Baiyangdian Lake, which has become a potential factor of water eutrophication [16]. Similarly, sediment P concentration is between 390 mg/kg and 810 mg/kg in the Three Gorges reservoir [15].…”
Section: Environment Influence Of Sediment Pmentioning
confidence: 99%
“…Zhang et al studied the adsorption and release of sediment P in the Three Gorges Reservoir and showed that the maximum adsorption capacity varied from 137.79 to 1975.5 mg/kg [15]. Dong et al, researched the adsorption and release characteristics of P in sediments of Baiyangdian Lake, which showed that P was a risk factor for water quality and ecosystems [16]. Experiments and the mass balance equation have been widely used to study the release flux of P in sediments, which is the effective method for exploring the influences of sediments on water quality [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The current research on the sediment P fractions is more focused on shallow lakes [5,7,15]. There have been few studies of the spatial and temporal distribution of the sediment P fractions in a subtropical mountain deep-water lake (or reservoir).…”
Section: Core Sediment P Fractionationmentioning
confidence: 99%
“…In recent years, sequential extraction procedures have been widely used in studies on the morphology of sediment P because it allows the rapid and effective extraction of the various forms of sediment P. Sediment P is usually divided into different forms, including exchangeable P (Ex-P), P bounded to Al and Fe oxides (Fe/Al-P), P bounded to calcium (Ca-P), inorganic P (Inorg-P) and organic P (Org-P) [4][5][6][7]. Although the total P (TP) content in the sediments reflects the eutrophic state of the lake to some extent, it is unable to predict the potential release risk and ecological hazard of P. The speciation distribution of P in the sediments can provide more information and help to understand the P cycles and P release tendency in the lake, and is one of the important parameters to predict the endogenous P release [8][9][10].…”
Section: Introductionmentioning
confidence: 99%